(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed primarily to investigate the effect of using the White Gunstone Model (PEOE) in science teaching on the development of scientific curiosity among primary school female students. To achieve this objective, the study adopted an experimental approach with a quasi-experimental one-group pretest–posttest design. The study sample consisted of (14( sixth-grade female students in Makkah, who were selected using purposive sampling. The instructional materials included a teacher’s guide and a student workbook designed in accordance with the White and Gunstone (PEOE) model. The research instruments comprised a Scientific Curiosity scale developed by the researcher. The results revealed statistically significant differences at the significance level (α ≤ 0.05) between the mean scores of the students in the pre- and post-applications of the Scientific Curiosity scale in favor of the post-application. These findings indicate that teaching science based on the White and Gunstone (PEOE) model has a positive effect on students’ Scientific Curiosity. Based on these results, the study recommends the adoption of the White and Gunstone (PEOE) model in science teaching and learning environments across different educational stages